El discurso y la praxis del desarrollo capitalista: ¿una adicción crónica irreversible? - López Oropeza, Mauricio (Nómadas. Critical Journal of Social and Juridical Science, 2009)
This essay presents a creative and critical analysis of the current situation related to the capitalist model centered in the market, from its extrinsic and intrinsic inconsistencies, through a reflection on its implacable effects in a society experiencing itself in a stage of planetary uncertainty, where its impacts on the environment can no longer be maintained, due to its excessive aim on exploitation and consumption, and due to the consequences of this model on the most excluded and vulnerable. This phenomenon is presented and analyzed as a chronic addiction, possibly irreversible, through an analogy with the dependence to artificial drugs as a way to deny reality. From there we present the 12 steps program of alcoholics and addicts anonymous, to apply it to the neoliberal development model, and from which is presented a possible new agenda towards an existential hangover that may lead our society to a sustainable soberness.